2012
DOI: 10.1051/epjconf/20122405009
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity measurements in volcano-tectonic area for geodynamic process study

Abstract: In the last ten years we carried out several radioactivity investigations in the aetnean area, a peculiar site characterized by both tectonic and volcanic features. In particular, continuous measurements in-soil radon gas carried out from 2001 until 2006 in the eastern flank of Mt. Etna, while several volcanic events occurred, showed a possible correlation between radon concentration and geodynamic activity, in particular magma uprising. We report in particular on the survey performed in order to determine ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…For the whole set of data reported in this work, we can reasonably retain the detected mineralogical phases and the glassy groundmass responsible for the content of radionuclides previously described. In particular, the activity concentrations reported in Table 3 put in evidence a 40 K value that appears to be high if compared with the literature data regarding radiological analyses in Etnean volcanic rocks [ 52 ].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…For the whole set of data reported in this work, we can reasonably retain the detected mineralogical phases and the glassy groundmass responsible for the content of radionuclides previously described. In particular, the activity concentrations reported in Table 3 put in evidence a 40 K value that appears to be high if compared with the literature data regarding radiological analyses in Etnean volcanic rocks [ 52 ].…”
Section: Resultsmentioning
confidence: 63%
“…The absorbed dose rate was estimated using Equation (2) and values range from 52.4 nGy h −1 to 71.4 nGy h −1 , with an average value of 65.3 nGy h −1 . The variability of the absorbed doses is attributable to the different lithologic components of the considered areas [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be noticed that that the radon activity concentration varies from a minimum of (7.4 ± 1.4) Bq L −1 for the site ID2 to a maximum of (164 ± 46) Bq L −1 for the site ID1, thus suggesting that the provenance of these drinking water samples is different and that they originate from different depths and pass through distinct geological strata. This uneven distribution of the specific activity may be dependent on the amount of Rn-222 in the aquifer rocks of different locations and on the residence time of water/rocks-soils in contact [36]. Specifically, the highest value was recorded for a site situated within the geological context of the "Calabrian-Peloritan arc" [37].…”
Section: Resultsmentioning
confidence: 98%
“…Elaborate research work conducted in Japan (Hirotaka et al, 1988;Igarashi et al, 1995) with Turkey (Inceoz et al, 2006;Friedmann et al, 1988) followed by Mt. Etna, Italy since 2001 (Imm è et al, 2005;Morelli et al, 2012). Precursory phenomena of radon in earthquake sequence were observed by Rastogi et al (1987) and precursory behavior of helium and radon observed for magnitude 5 earthquakes (Walia et al, 2005).…”
Section: Introductionmentioning
confidence: 98%